Structural properties and antioxidant activities of polysaccharide from fruit bodies of Pholiota nameko. Issue 11 (3rd June 2019) - Zhu, Zhen-Yuan; Pan, Li-Chao; Han, Dan; Sun, Hui-qing; Chen, Li-Jing
Abstract: A polysaccharide named PNP was extracted and purified from Pholiota nameko. The total sugar content of PNP was 95.29% and the molecular weight was 1.89 × 10 3 kDa. The structural features of PNP were investigated by the combination of chemical and instrumental analysis such as UV spectrophotometer, specific rotation determination, FT-IR, methylisation analysis and Congo red. The results showed that the optical rotation of PNP was +120° and that it had a triple-helical structure. Besides, PNP was mainly composed of glucose and mannose at the molar ratio of 4.24:1.00. The backbone of PNP was composed of (1→3)-linked-Glc and (1→3)-linked-Man whereas the branches of (1→3, 6)-linked- Glc, (1→3, 6)-linked-Man and T- Glc. Consistenting with the results of UV–Vis spectra, FT-IR spectroscopy and 1 H NMR, indicated that PNP was a complex of polysaccharides and polyphenols. In vitro antioxidant results suggested that PNP was processed with certain scavenging capacity. Abstract :